Faktor-Faktor Yang Mempengaruhi Price Earning Ratio Perusahaan LQ45 Di Bursa Efek Indonesia - Nia Yuniarsih (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
The purpose of this study was to determine the factors affecting price earningratio in LQ45 companies listed on the Indonesia Stock Exchange. This type ofresearch is a quantitative study with a sample of 40 companies starting in 2017 2018.The results of the study showed tha tthe variable Return on Assets, Return on Equity (ROE), Debt to Equity Ratio and Price Book Value together affect The Price Earning Ratio (PER). The t test shows theresults that Return on Assets has an influence on Price Earning Ratio, while Return on Equity,Debt to Equity Ratio and Price Book value do not affect the Price Earning Ratio.